A decellularized spinal cord extracellular matrix-gel/GelMA hydrogel three-dimensional composite scaffold promotes recovery from spinal cord injury via synergism with human menstrual blood-derived stem cells. Issue 30 (15th July 2022) - He, Wenhua; Zhang, Xuanxuan; Li, Xiangzhe; Ju, Dingyue; Mao, Tiantian; Lu, Yan; Gu, Yu; Qi, Longju; Wang, Qinghua; Wu, Qinfeng; Dong, Chuanming
Abstract : The DSCG, GelMA, and MenSCs were cross-linked by photoinitiators under UV irradiation to make composite scaffolds. The MenSC-encapsulated composite scaffolds were then transplanted into a rat model with complete spinal cord transection. Abstract : Spinal cord injury (SCI), as a serious disabling disease, is still haunted by lacking of effective treatments. We previously found that transplantation of menstrual blood-derived mesenchymal stem cells (MenSCs) promoted axon regeneration in rats with SCI, while the abominable microenvironment after the SCI inhibited the survival of stem cells after transplantation. Biomaterials can support the activity of stem cells and accelerate the functional reconstruction of the injured spinal cord. In this study, we constructed a novel composite scaffold consisting of the decellularized spinal cord extracellular matrix-gel (DSCG) and the GelMA hydrogel, which harbored high water retention, wettability, degradability and soft mechanical property. In vitro, the DSCG/GelMA composite scaffold provided a dual bionic microenvironment with optimized bioactive components and favorable microstructures for the adhesion, proliferation and differentiation of MenSCs. After that, we prepared MenSC-encapsulated DSCG/GelMA composite scaffolds to bridge the 2 mm gap in rats with completely transected SCI. The in vivo results showed that the combined use of the DSCG/GelMA composite scaffold with MenSCs improved the motor function, reduced the inflammatory response, promoted neuronal differentiation, and inhibited the proliferation of reactive astrocytes after spinal cord injury. Altogether, our study provided a promising novel therapeutic option of using bioactive materials synergistic with stem cells for the treatment of SCI.